The Capstone Design of Hybrid Power Plant for the Renewable Energy in the Airport - A Sadrina; M H B Satria; T P Sari; R D Issafira (BIOMEJ, 2023)
Currently, renewable energy sources are needed as a substitute for conventional energy sources because conventional energy sources will become decades in recent years. Renewable energy sources such as wind and solar have gained popularity and demand over the last decade. However, the output of this source depends on weather conditions. With these two sources, then we can produce the desired electric power. This project designs a hybrid power generation system model using wind and solar resources. This system can be implemented in areas around airports where large amounts of wind energy can be collected due to the high-speed movement of aircraft. At the same time, solar energy from the sun will also be collected. Eventually, the two energies will be collected simultaneously to charge the battery and be used for everyday life. The designed wind turbines are Savonius wind turbines which produce an average of 33.2-33.5 watts of electricity, and a Polycrystalline type solar panel with 200 WP.